Escolhas inteligentes em plantas: análise de aspectos comportamentais de espécies arbóreas - Oliveira Filho, Antônio Xavier de (2021)
The science of plant behavior aims to elucidate mechanisms that allow a plant organism to manage its internal complexity and response to external factors in order to maximize its fitness. Vegetable behavior can be visualized in changes that affect the individual's size and shape, such as growth and disposal of parts. Plants are able to perceive environmental changes and develop responses, even being able to distinguish the identity of the neighbor and change their behavior. This work investigated the behavioral strategies of plant species when subjected to interspecific interactions in the early stages of development. Individual’s strategies will be classified into three different types of behavior: competitive tolerance, avoid or confrontation. As a hypothesis, we have that species with greater leaf longevity will show slow growth and will behave with tolerance to competition while those with lesser leaf longevity will show fast growth and will have the behavior to competition confrontetion. For this, we germinate individuals of two species belonging to different phenological functional groups (late and early deciduous) that were planted in rhizotrons in pairs, with measurement of root, shoot and total growth. The hypothesis was partially corroborated, because the species A. cearesis (shorter longevity) showed behavior of competition confrontation, but with less growth when compared to the late deciduous species, L. ferrea. The latter didn't show an expected behavior to tolerate the neighbor and showed rapid growth. The species A. cearensis was shown to be more sensitive as to the perception of the neighbor, and L. ferrea was shown to be highly competitive for investing a lot in leaves and roots. The A. cearensis species's response of greater responsiveness demonstrates greater “behavioral intelligence”, an important strategy because it has a shorter period with leaves, so understanding the environment and making a decision to change the allocation of biomass can increase your chances of survival.